Disparities in Youth Arrest Across Racial and Ethnic Subgroups - Lehmann, Peter S. (Youth violence and juvenile justice, 2024)
An extensive body of research suggests that youth of color are more likely to experience an arrest than their White counterparts. Theoretically, these findings have been understood, at least in part, as the result of the differential deployment of law enforcement to areas with higher Black and Hispanic concentrations as well as stereotyped attributions of dangerousness and threat implicitly assigned to these suspects by police before and during encounters. However, previous studies typically have employed conventional racial/ethnic categorizations, which might obscure potential nuances in arrest disparities across subgroups. Using data on a statewide representative sample of adolescents from the 2018 Florida Youth Substance Abuse Survey (N = 54,611), these analyses reveal that the likelihood of a self-reported arrest is greatest among Haitian, West Indian/Caribbean, Dominican, and non-Hispanic Black youth. Further, Mexican and Puerto Rican adolescents have a higher risk of experiencing an arrest than members of other Hispanic subgroups.